2019
DOI: 10.3389/fnhum.2019.00209
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Attachment: From Behavior to Computational Neuroscience

Abstract: Cultural attachment (CA) refers to processes that allow culture and its symbols to provide psychological security when facing threat. Epistemologically, whereas we currently have an adequate predictivist model of CA, it is necessary to prepare for a mechanistic approach that will not only predict, but also explain CA phenomena. Toward that direction, we here first examine the concepts and mechanisms that are the building blocks of both the prototypical maternal attachment as well as CA. Based on existing robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 189 publications
0
1
0
Order By: Relevance
“…One reason for this approach was to create standardized, controlled, and thematically matched representations of culture fusion for testing our hypotheses. Furthermore, a large body of prior research has suggested that cultural icons, symbols, products, and practices, such as the ones depicted in our visual stimuli, can automatically activate corresponding cultural values, cognitions, mindsets, and goals (Hong et al, 2000; Wong & Hong, 2005; Yap et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this approach was to create standardized, controlled, and thematically matched representations of culture fusion for testing our hypotheses. Furthermore, a large body of prior research has suggested that cultural icons, symbols, products, and practices, such as the ones depicted in our visual stimuli, can automatically activate corresponding cultural values, cognitions, mindsets, and goals (Hong et al, 2000; Wong & Hong, 2005; Yap et al, 2019).…”
Section: Discussionmentioning
confidence: 99%